EU law after Lisbon - Biondi, Andrea; Eeckhout, Piet.; Ripley, Stefanie (Oxford : Oxford University Press, 2012)
The implementation of the Lisbon Treaty is profoundly changing many areas of EU law and policy. This volume gathers leading specialists in the field to analyse the implementation process and the directions of legal reform post-Lisbon, situating the Lisbon reforms in the broader context of on-going policy programmes.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Law -- European Union countries; Treaty on European Union -- (1992). -- (2007 Dec. 13.)